Analysis of Problems and Obstacles in Class Learning Processes at Islamic School Citra Taman Siswa - Dewi Rosaria Indah; Nur Hidayat (Kontribusia : Research Dissemination for Community Development, 2018)
This activity aims to analyse the problems & obstacles that occur in the learning process in the classroom. The subjects of this activity were several Math & English teachers in grades 4 and 6 of MI Citra Taman Siswa Menganti. In the implementation of this activity, the method used is a rubric (observation form). The results of the activity showed that there were several problems & obstacles in the learning process at MI Citra Taman Siswa including mastery of learning material, learning methods & lack of learning media covering 4 things: triggering question missed to stimulate students' curiosity, lack of explanation to understand concepts in Mathematics, lack of use of realia in mathematics learning & lack of use of media and learning resources in English classes.